Harmonisation of Shari'ah and Civil Law: a special reference to the concept of punishment - Awang, Abd. Rahman; Mohamad Yunus, Mohamad Ismail (Institut Kefahaman Islam Malaysia (IKIM), 2005)
Criminal law is one of the major areas that needs to be examined for the harmonization process between Civil Criminal Law and Islamic Criminal Law (hereinafter cited as CCL & ICL). Generally speaking, both systems are trying to protect and maintain peace and harmony in the society by introducing different kind of punishment in order to ensure that criminal activities will be reduced or prevented. For any offence committed, a prescribed punishment will be imposed. This mechanism can be seen from various punishments adopted by both systems depending on the nature and severity of the crimes. Their objectives however, are common and remain identical. ICL is a revealed law meant to protect public interest rather than to protect criminal though at times its rules are rather harsh and severe. This can be seen in the punishments of hudud and qisas. On the other hand, for the same offence, under CCL, the punishment is less severe, at time it is not considered as a crime at all, such as adultery, drinking of liquor, apostasy and accusation of zina. This is because the source, the philosophy and the value judgment are different. The main objective of this paper is to identify the similarities and the differences between the two systems in terms of their application and punishments. An attempt will be made to harmonize the laws of the two systems with practical and acceptable solutions. It is hoped that this paper will bring a new legal dimension towards eliminating the differences between CCL and ICL so that it can be implemented, in some areas, throughout the Muslim countries as a pilot study for the application of ICL as required by Islamic teachings.